Significant Barriers Influencing Green Design Application among the Contractors in Construction Industry - Heng , Yong Ming; Ahmad Rashid, Zul Zakiyuddin; Adnan, Hamimah (International Journal of Sustainable Construction Engineering and Technology, 2021)
This paper aims to find out the vital barriers that affecting the implementation of Green Design practice, which is part of the Green Supply Chain Management (GSCM) application in construction industry. GSCM is an innovative strategy that integrates environmental and social considerations with involving all parties in product (building) design stage, procurement, materials sourcing and selection, completion and handover to the ultimate users without overlooking the end-of-life management of the product. By the same time, GSCM also can improve both short and long-term competitiveness and profitability of the organisation. Green design application can reduce the environmental effects throughout the product lifecycle by minimising the resources and energy consumption. The objectives of this study are to determine and analyse the critical barriers that preventing Green Design related activities among contractors in construction industry. Quantitative research method with survey questionnaire was employed in this study. Total 450 sets of questionnaire were distributed with 21.8% response rate. The independent variables in this study was the barriers of Green Design implementation while the dependent variable was the adoption level of Green Design practice in construction industry. In short, four (4) barriers are identified, which were Government Supports, Company Resources, Knowledge and Information, and Financial issue barriers. Results of the study shown that Government Supports and Company Resources barriers were significant for Green Design practice. Significance of this research is to provide a better understanding of green practices, such as GSCM, to deal with current environmental issues and to realise the recent problems and obstacles faced by all construction players, so that further actions are required for a successful GSCM implementation in order to move towards a sustainable environment in the future.